1975
DOI: 10.1029/jb080i029p04094
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of surface deformation associated with volcanism

Abstract: Theoretical analyses of observed vertical and horizontal ground surface deformations near active volcanoes, particularly on Kilauea volcano in Hawaii, have led to useful estimates of the location and shape of subsurface magma reservoirs. One of the major shortcomings of the various existing elastic models is that they have very similar near‐field vertical deformations and they do not explain observed differences between vertical and horizontal deformations. Finite element models appear to offer better fits bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
176
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(194 citation statements)
references
References 11 publications
17
176
1
Order By: Relevance
“…Previous studies have shown that, in a homogeneous medium, prolate sources have u r /u z > 0.5, and oblate sources (sill-like) are characterized by u r /u z < 0.3 (Dieterich and Decker, 1975). For our best-fit model at Uturuncu, the predicted ratio is 0.46-suggesting that surface displacements could either be due to a single prolate source or a dipole.…”
Section: Homogeneous Half-space Modelsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous studies have shown that, in a homogeneous medium, prolate sources have u r /u z > 0.5, and oblate sources (sill-like) are characterized by u r /u z < 0.3 (Dieterich and Decker, 1975). For our best-fit model at Uturuncu, the predicted ratio is 0.46-suggesting that surface displacements could either be due to a single prolate source or a dipole.…”
Section: Homogeneous Half-space Modelsupporting
confidence: 51%
“…Decomposing InSAR line-of-sight (LOS) measurements into three Cartesian displacement vectors can help distinguish between reservoir geometries in the subsurface (e.g., Dieterich and Decker, 1975). The vertical or radial displacement profile alone is insufficient to identify reservoir geometry because the aspect ratio and depth of ellipsoidal sources can be varied such that profiles are indistinguishable (e.g., Fialko et al, 2001).…”
Section: Insarmentioning
confidence: 99%
“…The source epicenter is constrained by known points of lava effusion and by seismicity. Tilt data from CP2 and CP3 for individual inflations in May, with station radii measured from the assumed epicenter, yield a source depth about 700-800 m. However a cylindrical source is capable of producing similar surface displacement profiles [Dieterich and Decker, 1975], and analysis suggests that the top of the conduit pressure source is perhaps only a few hundred meters below the lava dome. This result provides an explanation for the lack of signals discerned at distant tilt stations.…”
Section: Discussionmentioning
confidence: 99%
“…In volcanology, numerical models have been developed mostly to compute displacements produced by magmatic intrusions into elastic ͑Dietrich and Decker, 1975;Cayol and Cornet, 1998;Williams and Wadge, 2000;Bonaccorso et al, 2005;Lungarini et al, 2005͒ or viscoelastic media ͑Folch et al, 2000Trasatti et al, 2003͒. Most of these studies account for the effect of topography and rheological heterogeneities on deformation.…”
Section: Numerical Modelingmentioning
confidence: 99%